Plan of Tsimpsean Indian Reserve No. 2, Coast District ... - Surveyor General Of British Columbia (University of Victoria Libraries, 2023)
Surveyed by S.P. Tuck and W.S. Jemmett, 1887; drawn by W.S. Jemmett, 1888. [Signed by P. O'Reilly, Indian Reserve Commissioner, no date.] [Approved by F.G. Vernon, Chief Commissioner of Lands and Works, 26 January 1892.] Map showing numerous Reserves along the Tsimpsean Peninsula including: Reserve No. 3 (Wil-Naskan-Caud); Reserve No. 4 (Shoo-Wah-Tlans); Reserve No. 5 (Cloyah); Reserve No. 6 (Willaclough); Reserve No. 7 (Point Vetch); Reserve No. 8 (Kh-Yex); Reserve No. 8 (Ensheshese); Reserve No. 9 (Kil-Cuts-E-En); Reserve No. 10 (Kh-Tah-Da); Reserve No. 11 (Scut-Tsap); Reserve No. 12 (Tymcowzan); Reserve No. 14 (Wilkaskamel); Reserve No. 15 (Toon); Reserve No. 16 (Lach-Mach)Reserve No. 17 on Somerville Island; Reserve No. 22 (Dash-Ken); Reserve No. 23 (Ksh-Room); Reserve No. 24 (Meanlaw). A reference map is also included as an inset map showing the location of all the reserves in this area. Land cover is not extensively described on the map but many rivers, channels, and islands are named including Work ...